2015
DOI: 10.1021/jacs.5b00146
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry-Breaking Charge Transfer in a Zinc Chlorodipyrrin Acceptor for High Open Circuit Voltage Organic Photovoltaics

Abstract: Low open-circuit voltages significantly limit the power conversion efficiency of organic photovoltaic devices. Typical strategies to enhance the open-circuit voltage involve tuning the HOMO and LUMO positions of the donor (D) and acceptor (A), respectively, to increase the interfacial energy gap or to tailor the donor or acceptor structure at the D/A interface. Here, we present an alternative approach to improve the open-circuit voltage through the use of a zinc chlorodipyrrin, ZCl [bis(dodecachloro-5-mesityld… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
123
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(141 citation statements)
references
References 56 publications
(176 reference statements)
5
123
1
Order By: Relevance
“…This implies that both the donor and acceptor photoexcitations can contribute to the achievable open circuit voltage as well as the photovoltaic performance of BHJ OSCs; this agrees with our earlier results [45] [68], 0.34-0.44 V for a range of donor-acceptor blends [69], 0.38 V for OC 1 C 10 -PPV:PCBM solar cells [12], and 0.30-0.60 V for BHJ OSCs [20]. Other low voltage offsets ( E DA/q − V j OC ) that have been reported recently are 0.25 V for an evaporated bilayer OSC [70], 0.23 V and 0.26 V for diketopyrrolopyrrole-thieno[2,3-f]benzofuran (DTD):PC 60 BM and DTD:naphthalene diimide acceptor-polymer (N2200) systems, respectively [71], and 0.34-0.40 V for BHJ OSCs [72], with which our calculated values also somewhat agree in the range.…”
Section: Discussionsupporting
confidence: 93%
“…This implies that both the donor and acceptor photoexcitations can contribute to the achievable open circuit voltage as well as the photovoltaic performance of BHJ OSCs; this agrees with our earlier results [45] [68], 0.34-0.44 V for a range of donor-acceptor blends [69], 0.38 V for OC 1 C 10 -PPV:PCBM solar cells [12], and 0.30-0.60 V for BHJ OSCs [20]. Other low voltage offsets ( E DA/q − V j OC ) that have been reported recently are 0.25 V for an evaporated bilayer OSC [70], 0.23 V and 0.26 V for diketopyrrolopyrrole-thieno[2,3-f]benzofuran (DTD):PC 60 BM and DTD:naphthalene diimide acceptor-polymer (N2200) systems, respectively [71], and 0.34-0.40 V for BHJ OSCs [72], with which our calculated values also somewhat agree in the range.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, when combined with the new PffBT‐T3(1,2)‐2 donor, which obtained a much higher PCE value over 10.0% with the PCBM acceptor, this acceptor yielded an excellent device performance about 6.90% without any further treatment. Very recently, Bartynski et al developed a novel nonfullerene small molecule acceptor D31 which was similar to the D27 acceptor . The UV–vis spectrum showed that this D31 molecule possessed a narrow absorption region from 450 to 600 nm and the CV result indicated this acceptor owned very low HOMO and LUMO energy levels about −6.00 and −3.88 eV, respectively.…”
Section: Nonfullerene Small Molecule Acceptorsmentioning
confidence: 99%
“…13 Thus, a substantial amount of work on organic photovoltaics has focused on minimizing the voltage loss required for exciton dissociation and to achieve the best possible compromise between photocurrent and photovoltage. 49 Fig. 1 demonstrates the empirical consequences of this compromise showing that the smaller the voltage difference between the band gap E g (divided by the elementary charge q ) and the actual V oc , the smaller will be the efficiency of photocurrent generation represented by the maximum external quantum efficiency (EQE max ) (see Table S1, ESI† for details).…”
mentioning
confidence: 99%